2015
DOI: 10.1002/cbic.201402669
|View full text |Cite
|
Sign up to set email alerts
|

Brevetoxin, the Dinoflagellate Neurotoxin, Localizes to Thylakoid Membranes and Interacts with the Light‐Harvesting Complex II (LHCII) of Photosystem II

Abstract: The brevetoxins are neurotoxins that are produced by the "Florida red tide" dinoflagellate Karenia brevis. They bind to and activate the voltage-gated sodium channels in higher organisms, specifically the Nav 1.4 and Nav 1.5 channel subtypes. However, the native physiological function that the brevetoxins perform for K. brevis is unknown. By using fluorescent and photoactivatable derivatives, brevetoxin was shown to localize to the chloroplast of K. brevis where it binds to the light-harvesting complex II (LHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 49 publications
(35 reference statements)
1
32
0
Order By: Relevance
“…Differences between toxic and low toxicity K. brevis strains in NPQ and reactive oxygen species (ROS) production supported this. 502…”
Section: Dinoagellatesmentioning
confidence: 99%
“…Differences between toxic and low toxicity K. brevis strains in NPQ and reactive oxygen species (ROS) production supported this. 502…”
Section: Dinoagellatesmentioning
confidence: 99%
“…Production of ROS was measured according to a previous protocol (Cassell et al ., ), with some modifications. A 25‐ml volume of Paulinella chromatophora culture (1.9 × 10 4 cells ml −1 , 0.25 μg Chl a ml −1 ) was transferred to 50‐ml flasks, illuminated under different intensities of white (0, 15, 30, 60, 90 and 120 μmol photons m −2 sec −1 ), blue (0, 5, 10, 20 and 40 μmol photons m −2 sec −1 ) or red (0, 5, 10, 20 and 40 μmol photons m −2 sec −1 ) light for 8 h. CM‐H 2 DCFDA (a cell‐permeable ROS indicator, 50 μg per tube; Life Technologies, http://www.thermofisher.com/us/en/home.html; catalog no.…”
Section: Methodsmentioning
confidence: 99%
“…In gel digestion and LC-Electrospray Ionization MS/MS (LC-ESI MS/MS) analysis was performed by the Proteomics and Mass Spectrometry Facility at the UMass Medical School as previously described. 9 …”
Section: Methodsmentioning
confidence: 99%
“…Using fluorescent and photoaffinity derivatives of brevetoxin, we demonstrated that exogenously applied brevetoxin localizes to the chloroplast of K. brevis where it interacts with two chloroplast proteins including thioredoxin (Trx). 9 Trx is the parent of a family of enzymes which mediate the redox state within a cell via thiol disulfide exchange. 10 Trx is converted from its inactive disulfide form to its active dithiol through reduction by thioredoxin reductase (TrxR).…”
Section: Introductionmentioning
confidence: 99%